Control of Spin Precession in a Spin-Injected Field Effect Transistor - Koo, Hyun Cheol; Kwon, Jae Hyun; Eom, Jonghwa; Chang, Joonyeon; Han, Suk Hee; Johnson, Mark (American Association for the Advancement of Science, 2009)
Spintronics increases the functionality of information processing while seeking to overcome some of the limitations of conventional electronics. The spin-injected field effect transistor, a lateral semiconducting channel with two ferromagnetic electrodes, lies at the foundation of spintronics research. We demonstrated a spin-injected field effect transistor in a high-mobility InAs heterostructure with empirically calibrated electrical injection and detection of ballistic spin-polarized electrons. We observed and fit to theory an oscillatory channel conductance as a function of monotonically increasing gate voltage.